GAINING WISDOM OVER THE YEARS: OLDER LATINOS EXCHANGING CANCER KNOWLEDGE. (11th November 2018) - Carrion, I; Estapé, T; Estapé, J; Nedjat-Haiem, F; Roberts, J; Lastra, A
Abstract: This study contributes to the limited body of literature that examines the beliefs and knowledge about cancer among immigrant Latino/a individuals aged 60 or older who reside in the Greater Tampa Bay area. The beliefs of older Latinos/as who have been diagnosed with cancer are explored in order to understand their advice to a family member or friend who has also been diagnosed with cancer as little is known about the transmission of this knowledge. The study presents the findings from 32 participants who were diagnosed with cancer, from a sample of 200 participants. The themes that emerged from the advice conveyed to family members and friends who had been diagnosed with cancer were possessing faith, obtaining a doctor, and seeking treatment. The participants' advice also included reliance on God, which was seen to be important in coping with a cancer diagnoses.